Inheritance of cowpea resistance to Cowpea aphid-borne mosaic virus - Silva, Jeferson Araújo; Costa, Antonio Félix da; Benko-Iseppon, Ana Maria; Guimarães, Lílian Margarete Paes; Leitão, Diego Arruda Huggins de Sá; Nicoli, Alessandro (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the inheritance of resistance to Cowpea aphid-borne mosaic virus (CABMV) in cowpea (Vigna unguiculata). The study was performed between parental genotypes IT85F-2687 (resistant) and 'BR-14 Mulato' (susceptible), generating F1, F2, and F7 populations and backcrosses with both parental genotypes. CABMV was inoculated on plants from all generations, which were then evaluated through visual inspection and description of characteristic symptoms. A chi-square test was performed after the phenotypic classification of all plants. A segregation proportion of 1:3 (resistant:susceptible) in population F2 and of 1:1 in population F7 was accepted, showing a recessive monogenic inheritance.